2013
DOI: 10.1007/s00268-013-2038-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Significance of Donor–Recipient Age Gradient as a Prognostic Factor of Graft Outcome in Living Donor Kidney Transplantation

Abstract: This study demonstrated that DRAG may serve as a prognostic factor for predicting graft outcomes after LDKT. Additionally, we showed that transplantation of older donor kidneys via living donation is justified in appropriately chosen age-matched recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…Shin et al . evaluated whether the effect of donor age was different according to recipient age (≤−21, −20 to −1, 0–20, and ≥ 21 years) in kidneys from deceased donors. The authors confirmed that a negative donor‐recipient age difference (recipients receiving kidneys from a donor younger than the recipient) was associated with greater death‐censored graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al . evaluated whether the effect of donor age was different according to recipient age (≤−21, −20 to −1, 0–20, and ≥ 21 years) in kidneys from deceased donors. The authors confirmed that a negative donor‐recipient age difference (recipients receiving kidneys from a donor younger than the recipient) was associated with greater death‐censored graft survival.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al 14 analyzed the DRAD and divided the patients into four groups: ≤ ‐21, ‐ 20 to – 1, 0‐20, and ≥21 years of difference between donor and recipient. A big difference was associated with more graft rejection episodes and higher serum creatinine levels beyond the first month post‐transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…La incidencia de rechazo durante el primer año reportada en esta cohorte fue inferior a lo reportado por otros estudios (18,9%), pudiendo explicar la alta tasa de supervivencia del injerto en nuestros pacientes a 5 años (88,4%) [6][7][8] .…”
Section: Discussionunclassified